Copper‐Catalyzed Direct Trifluoro‐ and Perfluoroalkylselenolations of Boronic Acids with a Shelf‐Stable Family of Reagents. Issue 19 (25th September 2017) - Glenadel, Quentin; Ghiazza, Clément; Tlili, Anis; Billard, Thierry
Abstract: Herein the copper‐catalyzed direct perfluoroalkylselenolation of aryl‐ and vinylboronic acids is described for the first time. The key to success is the design of new shelf‐stable perfluoroalkylselenolating reagents, namely perfluoroalkyl tolueneselenosulfonates. The reaction occurs at room temperature in the presence of commercially available catalyst and ligand in catalytic quantities. Abstract :